Pengaruh Perceraian Orang Tua Terhadap Perkembangan Emosional Anak - Riaka Ayu Lestari; Rara Insani; Prima Handayani (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
The first social environment for children creates the foundation for family behavior, forming attitudes and family life values. Parents are expected to be able to help children adapt to themselves and the environment to overcome problems realistically and lovingly. However, on the other hand, the family is often a source of conflict for other people. A disharmonious family atmosphere often gives rise to conflict between the two parents. One of the things that is the source of a child's biggest fear is separation from his parents. When a divorce occurs, children are the first victims of their parents' divorce. Divorce can cause emotional turmoil for the entire family and also affect the child's psychological side. Depressive states and anxiety levels are higher in children whose parents divorce. Children are also vulnerable to behavioral problems, crime and experience more conflict with peers after parental separation.